1987
DOI: 10.1029/ja092ia07p07413
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of amplitude‐modulated circularly polarized Alfvén waves for beta less than one

Abstract: We study the nonlinear properties of the amplitude‐modulated circulary polarized Alfvén wave for β < 1. The temporal behavior of the wave packet of the electromagnetic hybrid simulation is compared with a numerical solution of the derivative nonlinear Schrödinger (DNLS) equation. It is shown that the left‐hand‐polarized mode evolves into a shocklike structure due to the modulational instability. However, both cyclotron damping and a snowplow effect near the steepened wave packet suppress its further steepening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 32 publications
(21 reference statements)
2
21
0
Order By: Relevance
“…The presence of the modes in the above process is consistent with previous theories and simulations of parametric decay instabilities. 30,32,33 It is found that such parametric decay occurs more easily for ␤Ӷ1 and B p р1, consistent with the theoretical results by Jayanti and Hollweg. 34 For ␤у1, the instabilities are very sensitive to B p .…”
Section: A Wave Evolution Through Four Phases and Formation Of The Asupporting
confidence: 90%
“…The presence of the modes in the above process is consistent with previous theories and simulations of parametric decay instabilities. 30,32,33 It is found that such parametric decay occurs more easily for ␤Ӷ1 and B p р1, consistent with the theoretical results by Jayanti and Hollweg. 34 For ␤у1, the instabilities are very sensitive to B p .…”
Section: A Wave Evolution Through Four Phases and Formation Of The Asupporting
confidence: 90%
“…Terasawa et al [1986] and Machida et al [1987] examined a number of interactions between particles and large-amplitude waves which are similar to ones which arise in our simulations. Machida et al [1987] also make a detailed study of wave-particle interactions when wave trains are modulationally unstable and compare results with calculations using the derivative nonlinear SchrSedinger (DNLS) equation. The wave trains undergo steepening, and in this sense, the results are applicable to our study.…”
Section: Introductionmentioning
confidence: 63%
“…This instability has some of the required features in that the cascade is sustained and has waves traveling in opposite directions (but along B0) [e.g., Terasawa et al, 1986;Machida et al, 1987;Inhester, 1990;Vasquez, 1995]. Terasawa et al [1986] and Machida et al [1987] examined a number of interactions between particles and large-amplitude waves which are similar to ones which arise in our simulations. Machida et al [1987] also make a detailed study of wave-particle interactions when wave trains are modulationally unstable and compare results with calculations using the derivative nonlinear SchrSedinger (DNLS) equation.…”
Section: Introductionmentioning
confidence: 76%
“…By performing hybrid (kinetic ions + an electron fluid) simulations, Machida et al (1987) argues that the system automatically adjusts itself to a state described by the static approximation when ion kinetic effects are included. However, as time elapses, longitudinal mode grows and the static approximation is soon violated.…”
Section: Nonlinear Relation Among Phase and Frequency: Hall-mhd Equatmentioning
confidence: 99%